Testicular torsion based on material from the Department of Paediatric Surgery, Urology and Traumatology at Wladyslaw Buszkowski Children’s Hospital in Kielce during 2008–2013 - Sławek, Roman; Niedziela, Wojciech; Wolak, Przemysław (Medical Studies/Studia Medyczne, 2014)
Introduction: Among the causes of acute scrotum syndrome, testicular torsion undoubtedly causes the most serious consequences. The remaining aetiological factors are torsion of the testicular appendages and of the epididymis, epididymo-orchitis, testicular injury, incarcerated inguinal hernia, acute testicular hydrocele and idiopathic scrotal oedema. Torsion of the testis occurs as a result of a twisting of the testis around the vertical axis. This leads to venous occlusion and subsequently to arterial occlusion with ischaemia and necrosis of the gonad. Aim of the research: Determination of the possibilities of saving the testicle after torsion of the gonad. Material and methods: S ixty-eight cases of testicular torsion were analysed in boys aged 0–18 years who were treated during the period 2008–2013 in the Department of Paediatric Surgery, Urology and Traumatology in Kielce. The evaluation determined whether or not the gonad could be saved. The degree of macroscopically evident testicular necrosis was determined and the decision made concerning the saving or resecting the gonad. Further development of the saved testicle was monitored ambulatorily. Results: In 39 patients the testicle was removed due to necrosis, while in the remaining cases the gonad was saved. Torsion of the left testicle was more frequently observed. The symptoms of the torsion were: testicle pain, nausea and vomiting and, more rarely, abdominal pain. The symptoms occurred from 2 h to several days before reporting to hospital. Emergency surgery was performed. After the surgery ultrasonographic control covered the assessment of blood flow, echostructure and dimensions of the saved gonad (due to the possibility of atrophy after torsion). Conclusions: A patient who reports pain in the scrotal region should be approached as an emergency case, requiring immediate diagnostics and, very often, emergency surgical management. USG examination with the assessment of intratesticular vascular flow is a standard additional examination in the differential diagnostics of acute scrotum syndrome. Evaluation of the testicles is a necessary element of physical examination in all boys with abdominal pain.